(untitled) (Bangladesh Rice Journal, 2020)
The seed production potentialities of selected 20 hybrid rice combination were assessed in this study. Higher seed yield potentiality and earliness in maturity were two of the most important indicators for popularizing hybrid rice variety in Bangladesh. The field performance of the selected hybrid rice combinations were found to vary significantly for different traits except number of total spikelets per panicle showed insignificant variation among the hybrid rice genotypes. The highest number of tillers per plant was recorded in BRRI7A/BRRI31R (17.33) which was followed by BRRI10A/BRRI20R (16.33) and BRRI7A/BRRI20R (16.17). Maximum number of panicles per plant was produced by BRRI7A/BRRI31R (14.00) which was followed by BRRI10A/BRRI31R (13.07), and BRRI11A/BRRI31R (12.47). The highest number of filled spikelets per panicle was produced by BRRI7A/BRRI31R (48.20) which was followed by IR79156A/BRRI31R (47.83) and BRRI7A/BRRI10R (44.63) respectively. The highest value for percent out crossing rate (%OCR) was observed in the combination of BRRI7A/BRRI31R (50.23%) which was followed by BRRI10A/BRRI10R (46.40%). The highest value for grain yield per plant was recorded in BRRI7A/BRRI31R (8.17g) followed by BRRI10A/BRRI10R (7.85 g) and BRRI11A/BRRI15R (7.68 g), respectively. The lowest value for grain yield per plant was found in IR79156A/BRRI31R (3.97 g). Considering comparative study of floral traits, BRRI7A/BRRI31R hybrid rice combination has good commercial prospects but seed production potentiality under Bangladesh conditions needs to be estimated with fine tune. Bangladesh Rice j. 2019, 23(1): 13-20